Implementation of the Core Tax Administration System (CTAS) as a Digital Tax Solution: An Empirical Study on Taxpayer Satisfaction and Government Readiness - Agustina Indriani; Jombrik Jombrik; Rutinaias Haholongan (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2026)
Background: The digital transformation of tax administration has become a strategic priority for governments seeking to improve transparency, efficiency, and compliance. In Indonesia, the Core Tax Administration System (CTAS) represents a major step toward modernizing tax services within the Directorate General of Taxes, where user acceptance and institutional readiness are considered key determinants of success. Objectives:  This study examines the influence of taxpayer satisfaction and government readiness on CTAS implementation effectiveness in Indonesia's digital tax administration transformation. Methodology: A quantitative approach was employed using structured questionnaires distributed to taxpayers with experience using digital tax services, with multiple linear regression used to evaluate the effect of each independent variable. Findings: Taxpayer satisfaction has a positive and significant effect on CTAS implementation (t = 7.291, p = 0.000), reflected in perceptions of service accessibility, speed, data security, and information clarity. Government readiness, however, shows no statistically significant effect (t = 0.787, p = 0.433). Conclusions: Taxpayer satisfaction is a significant determinant of CTAS implementation success, whereas government readiness alone does not directly translate into taxpayer adoption without a positive user experience. These findings support the Technology Acceptance Model (TAM), underlining the need for simplified procedures, enhanced system stability, and responsive digital services to strengthen CTAS acceptance in Indonesia.